1840 Me. Rev. Stat. 709, ch. 169, §16 - (:unkn) unknown (General Publisher, 1840)
Required any person going armed with any dirk, dagger, sword, pistol, or other offensive and dangerous weapon to post a surety once a complaint was filed, having cause to fear an injury or breach of the peace. Surety not to exceed one year with appeals provided.
--
Keywords: POSSESSION - DANGEROUS PERSONS